Self-transformation through Education: An Analysis of Tara Westover's Struggles in the Memoir "Educated": SELF-TRANSFORMATION THROUGH EDUCATION - salsabila tazkia zamzam; Azmi Walidatul Muna; Zulfi Zumala; Izzul Huda (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2024)
This research examines Tara Westover's memoir, Educated, through Jack Mezirow's Transformative Learning Theory, which emphasizes critical reflection as a catalyst for profound personal change. The memoir chronicles Westover's journey from an isolated and oppressive upbringing to achieving academic success, illustrating education's role in fostering self-awareness, resilience, and identity transformation. Using qualitative methods, including literature analysis, the study focuses on the stages of transformative learning disorienting dilemma, self-examination, critical reflection, and reintegration as reflected in Westover's narrative. The findings reveal how education challenges ingrained beliefs, enabling individuals to navigate societal constraints and redefine their perspectives. Westover's academic journey, culminating in a doctorate from Cambridge University, underscores the power of education to transcend familial limitations and foster personal growth. This analysis highlights the dual function of education: as a means of acquiring knowledge and a transformative tool for personal empowerment. By linking individual experiences with societal structures, the study contributes to discussions on education's broader implications. Westover’s memoir serves as a compelling testament to the transformative power of education in reshaping identities, fostering adaptability, and enabling individuals to contribute meaningfully to society.